Mobile species’ responses to surrounding land use generate trade-offs and synergies among nature’s contributions to people - Sophie A. O’Brien; Jason M. Tylianakis; Dean P. Anderson; Andrea Larissa Boesing; Hao Ran Lai; Gaëtane Le Provost; Peter Manning; Margot Neyret; Nico Blüthgen; Kirsten Jung; Paul Magdon; Sandra Muller; et al. (Proceedings of the National Academy of Sciences, 2025)
Agricultural landscapes provide material, nonmaterial, and regulating contributions that affect human well-being (nature’s contributions to people, NCP). The responses of these NCP to land-use patterns depend on supporting biota with different habitat requirements, generating trade-offs and synergies. Predictions from spatially explicit modeling of NCP trade-offs and synergies could inform land-use decisions, but these do not typically account for the effects of land-use patterns on the movement of NCP-providing species, nor for interactions among NCP providers. To explore spatial trade-offs and synergies in eight indicators of NCP, we used Bayesian models that allow for interactions among land uses and among NCP using data from 150 grassland sites across rural Germany. We found that spatial arrangements of forest and open habitat influenced many beneficial NCP: acoustic diversity, birdwatching potential, natural enemy abundance, and pollination. In particular, the amount and proximity of land uses in the surrounding landscape, especially forest and open habitat, drove the supply of most NCP. However, detrimental NCP provided by smaller-bodied taxa (herbivory and pathogen infection) responded weakly to landscape factors. Multiple NCP provided by a given taxon responded differently to their surrounding landscape (e.g., bird-provided beneficial caterpillar predation and detrimental seed predation), leading to trade-offs and synergies among NCP over short distances. These were caused by different rates and directions of response to amount and location of land uses. Resulting spatial predictions revealed that the ratio of beneficial to detrimental NCP was maximized in areas with a high (≥95%) area of grassland or mixed forest-grassland (70:30%), rather than purely forest-dominated areas. This suggests promoting seminatural vegetation in agricultural landscapes to provide greater-than-additive benefits to net NCP supply.